A study of association between heart failure with preserved ejection fraction with hypertension and diabetes mellitus - Sarkar, Swapan; Biswas, Joydeep; Ghosh, Suprotim (Asian Journal of Medical Sciences, 2021)
Background: Heart failure is a common clinical entity which we come across in our daily practice and accounts for significant mortality and morbidity. The basic pathophysiology lies in the inability of the heart to pump adequate blood (output) to meet the demands of circulation/tissue or can do so only at the expense of elevated left ventricular filling pressure. Among various types of heart failure, heart failure with preserved ejection fraction (HFpEF) is still a poorly understood entity and several comorbidities such as hypertension, diabetes, coronary artery disease, obesity, and CKD are common association of HFpEF. Diabetes causes heart failure by increasing the risk of CAD and by direct injury to myocardium (cardiomyopathy). Hence, in this cross-sectional observational study, we assess the cardiovascular risk factors such as hypertension and diabetes mellitus in association with HFpEF.Aims and Objectives: This study aims to establish the hypothesis that hypertension and diabetes mellitus are associated with a predictor of HFpEF.Materials and Methods: Ninety patients were selected. NTproBNP, HbA1C, FBS, PPBS level, and blood pressure was measured and echocardiogram was performed to assess ratio of transmitral flow velocity and annular velocity (E/E’); left ventricular end-diastolic pressure; and left ventricular ejection fraction (LVEF).Results: The mean age was 64±7. Forty-two (46.67%) were men and 48 (53.33%) were female. Hypertension was present in 73 (81.11%) and diabetes in 44 (48.89%). E/E´, a parameter of LV diastolic function, showed positive correlation to both risk factors in study (r=0.653, p